THE EFFECT OF MARKETING MIX ON INDIHOME CUSTOMER LOYALTY AT PT TELEKOMUNIKASI INDONESIA TBK, LHOKSEUMAWE CITY - M. Subhan; Sahlatul Muna (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This research examines the influence of the marketing mix on IndiHome customer loyalty at PT Telekomunikasi Indonesia, Tbk Lhokseumawe City. The sample in this research was 98 IndiHome customers at PT Telekomunikasi Indonesia, Tbk Lhokseumawe City. The analytical tool used is multiple linear regression. The research results show that each of the product, price, place and promotion variables has a significant positive effect on customer loyalty, both partially and simultaneously